Answer:
c= 1
Step-by-step explanation:
To get rid of (c) on the right side, simply divide 2^n both side. But first collect like terms on the left side so you will get 2^n + 1 which you will then simplify the like term(2^n) and you will left with c= 1.
Simplify the following expression (x-8y)-(2x-4y)
Answer:
-x - 12y
Step-by-step explanation:
(x-8y)-(2x-4y)=
x-8y-2x-4y=
x-2x-8y-4y=
-x - 12y
Answer: -x - 4y
Step-by-step explanation:
(x-8y)-(2x-4y)
x-8y-2x+4y
-x-4y
A box of 120 crayons contains variations of three colors: blue, red, and purple. The ratio of blue crayons to red crayons is 11:2, and the ratio of the number of red crayons to purple crayons is 2:7. If all of the purple crayons were removed, how many crayons would be left in the box?
Answer: there would be 106,am not sure
Step-by-step explanation:
The equation __ describes the relationship
Answer:
y= 1/3x
Step-by-step explanation:
points on the graph
(0,0), (3,1)
function as per above two points:
y= 1/3x
Felipe is working to find the quotient of 6 and 3/4
Answer:
Felipe's answer is 8.
6 divided by 3/4
= 6 * 4/3
= 24/3
= 8
Answer:
8
Step-by-step explanation:
6÷3/4=6×4/3=8
Estimate the solution to the system of equations.
You can use the interactive graph below to find the solution.
-3x + 3y = 9
2x – 7y = -14
Answer:
x= -7/5 y=8/5
Step-by-step explanation:
1. choose a variable to eliminate (i chose 6)
2. multiply the first equation by 2 and the second equation by 3
3. now you have
-6x+6y=18
6x-21y=-42
and the x's can now cancel out when you add the equations together
4. after adding the equations, you get
-15y=-24
5. solve for y (y= 8/5)
6. now plug in 8/5 for the y in one of the original equations to solve for x. (i chose the first one)
7. -3x+3(8/5)=9
-3x+24/5=9
-3x=21/5
x= -7/5
What are the solutions of 2x²-6x+5=0?
Answer:
D
Step-by-step explanation:
a = 2 ; b = -6 ; c = 5
[-b±√b²-4ac]/2a=[-(-6)±√6²-4*2*5]/2*2
=[6±√√36-40]/4
=[6±√-4]/4
=[6±√i²*2²]/4
=[6±2i]/4
=2[3±i]/4
=3±i/2
= 3+i/2 or 3-i/2
2. A hemispherical water tank with a volume of 2094 m will have a radius of which
length?
?
a. 5 m
b. 25 m
c. 2.5 m
d. 10 m
Find the sum of the first eight terms of the geometric series 1 + 2 + 4 + ...
Answer:
The sum of all of the terms would be 255
Step-by-step explanation:You would continue to multiply all of the answers by 2 until you hit 128. Then you would add all of them together 128+64+32+16+8+4+2+1=255
Need help ASAP!! Thank youu!
Answer:
The answer is 7.
Step-by-step explanation:
If you want to find what FE is, you have subtract GF from GE (GE - GF = FE).
Since GE = 13 and GF = 6, you have to subtract 6 from 13 which equals 7.
(13 - 6 = 7)
Which ordered pair comes from the table?
can someone do my ixl its 6th grade math!! only 3 and you have to get 85 and higher i will give 25 points!! and mark as brainlist
Answer:
Okkk I will answer
Answer:
what question do you have?
Step-by-step explanation:
help me help me help me asap
Answer:
9 cubic feet
Step-by-step explanation:
Assuming that the garden box is a rectangular prism, its volume is:
[tex]4\dfrac{1}{2} \cdot 4 \cdot \dfrac{1}{2}=9 \text{ ft}^3[/tex]
Hope this helps!
Solution,
Length(L)=4 1/2 ft
Breadth(b)= 4 ft
Height(H)=1/2 ft
Now,
Volume=L*B*H
= 4 1/2*4*1/2
=9/2*4*1/2
= 9 cubic feet
Hope it helps
Good luck on your assignment
Alegbra 4 questions giving brainlist!
Answer:
1) 4
2) 1
3) -7
4) 13
Step-by-step explanation:
Instructions:
a) Subtract or add the slope from each side
( it doesn't matter which one you pick )
b) Subtract or add the # next to the slope from each side
( it doesn't matter which one you pick )
c) Divide Each number by the slope
d You have you answer
____________________________________________
1) 9x - 35 = - 7x + 29
+7x + 7x
_____________________
16x - 35 = 29
+ 35 +35
_____________________
16x = 64
_____________________
16 16
x = 4
2). - 2x - 2 = 9x - 13
+2x +2x
_____________________
- 2 = 11x - 13
+ 13 + 13
_____________________
11 = 11x
_____________________
11 11
1 = x
3). 3x + 29 = - 5x - 27
+5x + 5x
_____________________
8x + 29 = - 27
-29 -29
_____________________
8x = -56
_____________________
8 8
x = -7
4). x - 11 = 3x - 37
- x - x
______________________
-11 = 2x - 37
+37 +37
______________________
26 = 2x
_______________________
2 2
13 = x
Hope this helps! (:
find the coordinates of D' after a Glide reflection of the triangle: translation 1 unit up and 5 units left and reflection across y= 3. Write your answer in (a,b). Part 2a
Answer:
D' = (-2, 1)
Step-by-step explanation:
Translating the point D one unit up and five units left moves it to (-2, 5)
Reflecting it across y=3 moves it from (-2, 5), to (-2, 1)
Answer:
D = (-2, 1)
This answer is 100% right hope it helps
What segment is a reflection of segment ab over the line x=1
Answer:
The correct answer is: (Line segment E F)
Please answer correctly !!!! Will mark brainliest !!!!!!!!!
Answer:
[tex]=\left(x-4\right)^2[/tex]
Step-by-step explanation:
[tex]x^2-8x+16\\\mathrm{Rewrite\:}x^2-8x+16\mathrm{\:as\:}x^2-2x\cdot \:4+4^2\\x^2-8x+16\\\mathrm{Rewrite\:}16\mathrm{\:as\:}4^2\\=x^2-8x+4^2\\\mathrm{Rewrite\:}8x\mathrm{\:as\:}2x\cdot \:4\\=x^2-2x\cdot \:4+4^2\\\mathrm{Apply\:Perfect\:Square\:Formula}:\quad \left(a-b\right)^2=a^2-2ab+b^2\\a=x,\:b=4\\=\left(x-4\right)^2[/tex]
Answer:
0
Step-by-step explanation:
Since it is asking you to factor out the quadratic, you need to make it equal zero first. -4 times -4 is both 16 and -8. So that means (x-4)^2
Originally the dimensions of a rectangle were 20cm by 23cm. When both dimensions were decreased by the same amount, the area of the rectangle decreases by 120. Find the dimensions of the rectangle.
what is 9x=4.5 if u can solve this u are very smart
Answer:
x = 1/2
Step-by-step explanation:
9x=4.5
Divide each side by 9
9x/9 = 4.5/9
x = 45/90
x = 1/2
Answer:
x = 1/2 or x = 0.5
Step-by-step explanation:
9x = 4.5/9
= 45/90
= 1/2 or 0.5
Hope this helps, and please mark me brainliest if it does!
Pleaseee help meee struggling currently
Answer: 2908.92435 inches.
Step-by-step explanation for shape 1: A = 2(wl + hl + hw) = 2 · (30 · 13 + 13 · 13 + 13 · 30) = 1,898 inches.
Step-by-step explanation for shape 2:
Using the formulas:
A=2AB+(a+b+c)h
AB=s(s﹣a)(s﹣b)(s﹣c)
s=a+b+c
2
Solving for A:
A=ah+bh+ch+1
2﹣a4+2(ab)2+2(ac)2﹣b4+2(bc)2﹣c4=9·30+13·30+9·30+1
2·﹣94+2·(9·13)2+2·(9·9)2﹣134+2·(13·9)2﹣94≈1010.92435
Step-by-step explanation for total volume: 2908.92435 inches.
Answer: 6825 in^3
Step-by-step explanation:
First divided the whole shape into two shapes.
The first shape will be a rectangular prism and the second shape will be a triangular prism.
The rectangular prism will have a length of 13, a width of 30 and the height of 13.
Now find the volume of the rectangular prism by multiplying the length by the width then by the height.
V= 13 * 30 * 13
V = 5070
This means the volume of the rectangular prism is 5070 cubic inches.
Now will will need to find the volume of the triangular prism.
The triangular prism has a triangle at the base, with a base of 9 and a height of 13. If you multiply the the area of the base by the whole height of the triangular prism which is 30 then you will get the volume.
Find the area of the base.
The area is base time height times 1/2.
A = 9 * 13 * 1/2
A = 58.5
Now multiply the area by 30.
58.5 * 30 = 1775
Finally, add both volumes to find the full volume of the figure.
5070 + 1775 = 6825
Please answer correctly !!!!! Will mark brainliest !!!!!!!!
Answer:
k(-7) = = -89
Step-by-step explanation:
k(t) = 10t -19
Let t = -7
k(-7) = 10*-7 -19
= -70-19
= -89
Answer:
-89
Step-by-step explanation:
K(t) = K(-7)
10 is being multiplied by t. t = -7
so:
10(-7) = -70
-70 - 19 = -89
Hope this helps!
Match the parabolas represented by the equations with their foci.
Answer:
Step-by-step explanation:
Before we begin this, there are a few things that need to be said and a few formulas you need to know. First is that we need to use the work form of a parabola, which is
[tex]y=a(x-h)^2+k[/tex]
All of the parabolas listed in blue highlight open either up or down, and this work form represents those 2 options. The only thing we need to know is that if there is a negative sign in front of the a, the parabola opens upside down like a mountain instead of up like a cup.
Another thing we need to know is how to find the focus of the parabola. The formula to find the focus for an "up" parabola is (h, k + p) and the formula to find the focus for an upside down parabola is (h, k - p). Then of course is the issue on how to find the p. p is found from the a in the above work form parabola, where
[tex]p=\frac{1}{4|a|}[/tex] .
In order to accomplish what we need to accomplish, we need to put each of those parabolas into work form (as previously stated) by completing the square. I'm hoping that since you are in pre-calculus you have already learned how to complete the square on a polynomial in order to factor it. Starting with the first one, we will complete the square. I'll go through each step one at a time, but will provide no explanation as to how I got there (again, assuming you know how to complete the square).
[tex]y=-x^2+4x+8[/tex] and, completing the square one step at a time:
[tex]-x^2+4x=-8[/tex] and
[tex]-(x^2-4x+4)=-8-4[/tex] and
[tex]-(x-2)^2=-12[/tex] and
[tex]-(x-2)^2+12=y[/tex]
From this we can see that the h and k values for the vertex are h = 2 and k = 12. Now to find p.
[tex]|a|=1[/tex], ∴
[tex]p=\frac{1}{4(1)}=\frac{1}{4}[/tex]
Using the correct focus formula (h, k - p), we get that the focus is
[tex](2, 12-\frac{1}{4})[/tex] which simplifies to (2, 11.75) which is choice 2 in your options.
Now for the second one (yes, this takes forever...)
[tex]y=2x^2+16x+18[/tex] and completing the square one step at a time:
[tex]2x^2+16x=-18[/tex] and
[tex]2(x^2+8x+16)=-18+32[/tex] and
[tex]2(x+4)^2=14[/tex] and
[tex]2(x+4)^2-14=y[/tex]
From this we can see that the vertex is h = -4 and k = -14. Now to find p from a.
[tex]|a|=2[/tex], ∴
[tex]p=\frac{1}{4(2)}=\frac{1}{8}[/tex] .
Using the correct focus formula for an upwards opening parabola (h, k + p),
[tex](-4, -14+\frac{1}{8})[/tex] which simplifies down to (-4, -13.875) which is choice 3 in your options.
Now for the third one...
[tex]y=-2x^2+5x+14[/tex] and completing the square step by step:
[tex]-2x^2+5x=-14[/tex] and
[tex]-2(x^2-\frac{5}{2}x+\frac{25}{16})=-14-\frac{50}{16}[/tex] and
[tex]-2(x-\frac{5}{4})^2=-\frac{137}{8}[/tex] and
[tex]-2(x-\frac{5}{4})^2+\frac{137}{8}=y[/tex]
From that we can see the vertex values h and k. h = 1.25 and k = 17.125. Now to find p.
[tex]|a|=2[/tex], ∴
[tex]p=\frac{1}{4(2)}=\frac{1}{8}[/tex]
Using the correct focus formula for an upside down parabola (h, k - p),
[tex](1.25, 17.125-\frac{1}{8})[/tex] which simplifies down to (1.25, 17) which is choice 4 in your options.
Now for the fourth one...
[tex]y=-x^2+17x+7[/tex] and completing the square step by step:
[tex]-x^2+17x=-7[/tex] and
[tex]-(x^2-17x)=-7[/tex] and
[tex]-(x^2-17x+72.25)=-7-72.25[/tex] and
[tex]-(x-8.5)^2=-79.25[/tex] and
[tex]-(x-8.5)^2+79.25=y[/tex]
From that we see that the vertex is h = 8.5 and k = 79.25. Now to find p.
[tex]|a|=1[/tex], ∴
[tex]p=\frac{1}{4(1)}=\frac{1}{4}[/tex]
Using the correct formula for an upside down parabola (h, k - p),
[tex](8.5, 79.25-\frac{1}{4})[/tex] which simplifies down to (8.5, 79) and I don't see a choice from your available options there.
On to the fifth one...
[tex]y=2x^2+11x+5[/tex] and again step by step:
[tex]2x^2+11x=-5[/tex] and
[tex]2(x^2+\frac{11}{2}x+\frac{121}{16})=-5+\frac{242}{16}[/tex] and
[tex]2(x+\frac{11}{4})^2=\frac{81}{8}[/tex] and
[tex]2(x+\frac{11}{4})^2-\frac{81}{8}=y[/tex]
from which we see that h = -2.75 and k = -10.125. Now for p.
[tex]|a|=2[/tex], ∴
[tex]p=\frac{1}{4(2)}=\frac{1}{8}[/tex]
Using the correct focus formula for an upwards opening parabola (h, k + p),
[tex](-2.75, -10.125+\frac{1}{8})[/tex] which simplifies down to (-2.75, -10) which is choice 1 from your options.
Now for the last one (almost there!):
[tex]y=-2x^2+6x+5[/tex] and
[tex]-2x^2+6x=-5[/tex] and
[tex]-2(x^2-3x+2.25)=-5-4.5[/tex] and
[tex]-2(x-1.5)^2=-9.5[/tex] and
[tex]-2(x-1.5)^2+9.5=y[/tex]
from which we see that h = 1.5 and k = 9.5. Now for p.
[tex]|a|=2[/tex], ∴
[tex]p=\frac{1}{4(2)}=\frac{1}{8}[/tex]
Using the formula for the focus of an upside down parabola (h, k - p),
[tex](1.5, 9.5-\frac{1}{8})[/tex] which simplifies down to (1.5, 9.375) which is another one I do not see in your choices.
Good luck with your conic sections!!!
will mark brainliest!! factor the following equation: f(x)=3x²+7x+2
Answer:
(x + 2) (3x + 1)
Step-by-step explanation:
3x² + 7x + 2
3x² + 6x + x + 2
3x(x + 2) + 1(x + 2)
(x + 2) (3x + 1)
Find the circumference of the circle to the nearest hundredth. Use 3.14 for π. Radius 21 cm.
Answer:
[tex]131.95[/tex] [tex]cm[/tex]
Step-by-step explanation:
[tex]C=2 \pi r[/tex]
[tex]C=2 \pi \times 21[/tex]
[tex]C=42\pi[/tex]
[tex]C \approx 131.946891451[/tex]
Ping lives at the corner of 3rd Street and 6th Avenue. Ari lives at the corner of 21st Street and 18th Avenue. There is a gym Two-thirds the distance from Ping's home to Ari's home.
x = (StartFraction m Over m + n EndFraction) (x 2 minus x 1) + x 1
y = (StartFraction m Over m + n EndFraction) (y 2 minus y 1) + y 1
Where is the gym?
Answer: (15th street, 14th Avenue)
Step-by-step explanation:
Given the following :
Ping's residence = (3rd street, 6th Avenue)
Ari's residence = (21st street, 18th Avenue)
Gym location = 2/3 the distance of Ping's residence to Ari's residence
So, distance between Ping's home to Ari's home
Distance = (21st street, 18th Avenue) - (3rd street, 6th Avenue)
Distance = (21 - 3) street, (18 - 6) avenue
Distance between ping and Ari = (18th , 12th )
Gym distance = 2/3 of distance between ping and Ari
Gym distance = 2/3 × (18), 2/3 ×(12)
Gym distance = (12, 8)
Gym location = Ping's location + gym distance
Gym location = (3rd street, 6th Avenue) + (12th street, 8th Avenue)
Gym location = (15th street, 14th Avenue)
Answer:
d) 15th Street and 14th Avenue
describe fully the single transformation that maps triangle a onto triangle b
Answer:
Reflection about y=2
Step-by-step explanation:
Triangle A should be reflected about y=2 to map it onto Triangle B.
Answer:
reflection across y=2
Step-by-step explanation:
a store employees 11 women and 12 men.what percentage of employees are men?
Answer:
easy just find the total of how many people work there then put that no. as a denominator and put 12 on the numerator then times it by 100 and the answer should be 52.2% or 52.17%
Answer:
52.2% or 52.17%
12 men
Total = 23
12 / 23 =
Draw the following lines and label them with the matching letter. Then write an equation for each. Slope is 0, y-intercept is 5 Slope is 2, y-intercept is -1 Slope is -2, y-intercept is 1 Slope is -12, y-intercept is -1
Answer:
See explaination:
Graphs are on the right, equations are on the left, and they are color coded.
Step-by-step explanation:
Brainliest question please help me answer my question please
Answer:
Step-by-step explanation:
The area for a trapezoid is
[tex]A=\frac{1}{2}h(b_{1}+b_{2})[/tex]
h is the length of ST, one of the bases is the length of MK, and the other base is the length of AS. First we'll find h:
The coordinates for S are (0, -2) and T are (1, 2). Using the distance formula:
[tex]d=\sqrt{(1-0)^2+(2-(-2))^2[/tex] and
[tex]d=\sqrt{17}[/tex]. So h = √17
Now for the length of MK. The coordinates for M are (-7, 4) and for K (5, 1). Using the distance formula again:
[tex]d=\sqrt{(-7-5)^2+(4-1)^2}[/tex] and
[tex]d=\sqrt{(-12)^2+(3)^2}[/tex] so
[tex]d=\sqrt{153}[/tex] which simplifies to
[tex]d=3\sqrt{17}[/tex]. So MK = 3√17.
Now for the length of AS. The coordinates for A: (-4, -1) and for S: (0, -2). Using the distance formula one more time:
[tex]d=\sqrt{(-4-0)^2+(-1-(-2))^2}[/tex] and
[tex]d=\sqrt{(-4)^2+(1)^2}[/tex] and
[tex]d=\sqrt{17}[/tex]. So AS = √17.
Now we can fill in our area formula:
[tex]A=\frac{1}{2}(\sqrt{17})(3\sqrt{17}+\sqrt{17})[/tex]
Simplifying a bit:
[tex]A=\frac{1}{2}(\sqrt{17})(4\sqrt{17})[/tex] and simplifying a bit more:
[tex]A=\frac{4*17}{2}[/tex] and
A = 34
If 48 % of students in a certain college are female and there are 1,440 female students, what is the total number of students in the college? Please show work
Answer:
The total number of students in the college is 3,000.
Step-by-step explanation:
[tex]\frac{48}{100}=\frac{1,440}{x}[/tex] Set up a proportion.
[tex]48x=144,000[/tex] Cross-multiply.
[tex]x=3,000[/tex] Divide both sides by 48.
What is the answer to this problem.
Answer:
[tex]2a^2 + 3x - 2a[/tex]
Step-by-step explanation:
[tex] (6a^2 + 3x) - (4a^2 + 2a) = [/tex]
The first set of parentheses is unnecessary and can be removed.
[tex] = 6a^2 + 3x - (4a^2 + 2a) [/tex]
To remove the second set of parentheses, you must distribute the negative sign to its left as if it were a -1 multiplying the quantity inside the parentheses.
[tex] = 6a^2 + 3x - 1(4a^2 + 2a) [/tex]
[tex] = 6a^2 + 3x - 4a^2 - 2a [/tex]
Now combine like terms. Like terms are terms with the same variable part.
[tex] = 2a^2 + 3x - 2a [/tex]